Aplicações de Matrizes e Sistemas Lineares Utilizando do Scilab e o Geogebra - Natália Aparecida Sylvestrino Pereira (2021)
This work presents concepts relative to Matrices and Linear Systems, taught in the 2nd year of High School, intended to solve contextualized problems through free educational software tools, Scilab and GeoGebra, which can result in a more dynamic approach of the contents.